Antiblackness, Black Joy, and Embracing a Humanizing Critical Sociocultural Knowledge (HCSK) for Teaching: Lessons From Schooling in the Time of COVID-19. (3rd July 2021) - Brown, Keffrelyn D.; Brown, Anthony L.
Abstract : In this critical reflective analysis, we explore the nature of schooling for Black children and youth before and during the COVID-19 pandemic and envision its transformative possibilities. We draw from Black intellectual thought around antiblackness, Black joy, and Brown?s humanizing critical sociocultural knowledge to interrogate our own pandemic case as two Black education scholars working from home while also supervising the virtual schooling of our two Black children from March 2020?March 2021. While no lessons learned justify the pain of COVID-19, we share key insights and wisdom we gained during our quarantine that ask us to re-imagine the futures of schooling for Black students.